International Student Recruitment and Mobility in Non-Anglophone Countries: Theories, Themes, and Patterns - Alex, Alexander Erickson (Journal of International Students, 2023)
In International Student Recruitment and Mobility in Non-Anglopone Countries, Hans de Wit, Ekaterina Minaeva, and Lizhou Wang offer a detailed analysis and global contextualization of current recruitment and mobilization strategies in a host of different countries and regions around the world. Utilizing perspectives from specialized co-authors, each chapter examines the historical and modern context of the specific country along with its short and long-term goals, strengths, weaknesses, threats, opportunities, and more. The book provides extensive international student recruitment and mobilization recommendations for practioners and education policy advisors in the higher education industry around the globe.